Konsep Negosiasi dalam Konflik Transnasional Studi Kasus: Pemerintah Indonesia dan PTTEP Australasia dalam Insiden Kilang Minyak Montara 2009-2012 - Deyastrie, Khania; Windiani, Reni (Journal of International Relations, 2018)
On 21st August 2009 blow up occur at Montara Platform belong to PTTEP Australasia. This research aims to explain step-by-step prosecution claim negotiation on Montara Platform Incident from the incident occur until 2012 thru non-court lines. By using G.R. Berridge negotiation concept theory and comparing it to the field discovery, research found that PTTEP Australasia find ways to postpone finalizing the deal in MoU Dual Track in order to avoid responsibilities on Montara case. PTTEP Australasia also hide behind PTT Public Company Limited and Thailand’s Government from Indonesia’s claim. In the other hand Government of Indonesia also have strategies gain agreement by using publication, Neutral Committee, deadline, and continuous meeting to keep negotiation momentum even tough by the end of negotiation MoU dual track left floating without final agreement nor approval signatures.